The Ploidy State as a Determinant of Hepatocyte Proliferation - Wilson, Sierra R.; Duncan, Andrew W. (Seminars in Liver Disease, 2023)
The liver's unique chromosomal variations, including polyploidy and aneuploidy, influence hepatocyte identity and function. Among the most well-studied mammalian polyploid cells, hepatocytes exhibit a dynamic interplay between diploid and polyploid states. The ploidy state is dynamic as hepatocytes move through the “ploidy conveyor,” undergoing ploidy reversal and re-polyploidization during proliferation. Both diploid and polyploid hepatocytes actively contribute to proliferation, with diploids demonstrating an enhanced proliferative capacity. This enhanced potential positions diploid hepatocytes as primary drivers of liver proliferation in multiple contexts, including homeostasis, regeneration and repopulation, compensatory proliferation following injury, and oncogenic proliferation. This review discusses the influence of ploidy variations on cellular activity. It presents a model for ploidy-associated hepatocyte proliferation, offering a deeper understanding of liver health and disease with the potential to uncover novel treatment approaches.
Keywords: polyploidy; liver regeneration; liver injury; liver repopulation; ploidy conveyor